Strength training and growth hormone: effects on bone of Wistar rats - Castoldi, Robson Chacon [UNESP]; Giometti, Ines Cristina; Ozaki, Guilherme Akio Tamura; Garcia, Thiago Alves; Ueno, Melise Jacon Peres [UNESP]; Fernandes, Fernanda [UNESP]; Dornelles, Rita Cássia Menegati [UNESP]; Louzada, Mario Jefferson Quirino; Filho, José Carlos Silva Camargo [UNESP]; Belangero, William Dias (Springer Nature, 2021)
Introduction: The use of growth hormone (GH) in several sports has also been observed, becoming a problem for antidoping control agencies in the high-performance sports environment. In addition, the use of this substance may pose a risk, expose users to potential health problems and bone alterations. Objective: The objective of the present study was to verify the effects of muscular strength training and application of a GH protocol on mineral density, bone strength, and trabecular tissue. Methods: 40 Wistar rats, 60 days old, were used. The animals were divided into four groups: control (C), control and application of GH (GHC), muscular strength training (T), and muscular strength training with the application of GH (GHT). Animals of the GHC and GHT groups received administration of 0.2 IU/kg of GH prior to perform the T protocol. The animals of the T and GHT groups performed four series of 10 jumps, 3×/week, for 4/weeks. The values of bone mineral density (BMD), bone strength (F-max), and Micro Computed Tomography (MCT) were obtained. Results: An increase in the BMD variable was observed in all experimental groups (C = 0.110 ± 0.005; GHC = 0.134 ± 0.05; T = 0.127 ± 0.004; GHT = 0.133 ± 0.008 g/cm2) (C vs GHT p < 0.05). No statistical difference was observed for the F-max variable. For MCT, all experimental groups presented an increase in the number of trabeculae (Tb.N) (C = 1.10 ± 0.22; GHC = 1.79 ± 0.07; T = 1.91 ± 0.04; GHT = 1.91 ± 0.09) (p < 0.05). Conclusion: It was concluded that both GH and T were able to promote increases in BMD and Tb.N; however, no significant difference was observed for the F-max.
Keywords: Anabolics; Bone mineral density; Bone strength; Microstructure trabecular; Physical training